Pelaksanaan Program Tahsin Tahfidz Fathona (TATAFA) di SD Islam Terpadu Fathona Palembang - Setyaningsih, Kris; Rosidah, Maila; Safitri, Dian (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyze the implementation of the tahsin tahfidz fathona program at Fathona Integrated Islamic Elementary School in Palembang. This research employs a qualitative method with a descriptive qualitative approach. The study involves 20 informants, consisting of the program coordinators, Tahfidz teachers, and students. Data collection techniques include observation, interviews, and documentation. Data analysis techniques involve data reduction, data presentation, data verification, and conclusion drawing. The validity test of this research data uses source triangulation and technique triangulation. The results and discussion indicate that the Tahsin Tahfidz Fathona program has been implemented effectively. This is evident through guidance, coordination, motivation, and continuous communication in the program’s execution. The implementation includes adherence to Tajwid rules, reading fluency, understanding of Makharijul Huruf, assessments and evaluations, teacher feedback, repetition of memorization (Muraja’ah), accuracy and fluency in reading, and the ability to connect verses during the program.